Diplomacy and Negotiation In The Liberation Of Abu Sayyaf Hostagee - Nabila Husnul Khotimah; Saili Rahma Fidrianti; Rizky Andika Putra; Yusawinur Barella; Ori Fahriansyah (PT Syamilah Literasi Islami, 2024)
This study explores the involvement of the Abu Sayyaf Group in international relations, focusing on their activities of piracy and hostage-taking, and the role of diplomacy in hostage release. The research aims to analyze the chronological events of abduction and the diplomatic negotiations that follow. Utilizing a qualitative approach, the study examines various case studies of Abu Sayyaf’s kidnappings and the subsequent employs hostage-taking as a strategic tool to finance their operations, often targeting foreign nationals to laverage international attention. Diplomatic negotiations, both official and unofficial, play a crucial role in securing the release of hostages. The study concludes that effective diplomacy, infolving international pressure and regional cooperation, is essential in resolving hostage situations. This research highlight the importance of strategic communication and negotiation skills in international diplomaccy and counterterrorism efforts.